2003
DOI: 10.1016/s0735-1097(03)00091-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular septal and apex pacing for optimal pump function in canine hearts

Abstract: During ventricular pacing, LV pump function is maintained best (i.e., at SR level) when pacing at the LV septum or LV apex, potentially because pacing from these sites creates a physiological propagation of electrical conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 35 publications
8
116
0
3
Order By: Relevance
“…Our finding of lower cardiac mortality as well as death from pump failure with an apical LV lead position is in keeping with experimental and clinical studies showing that LV apical pacing is physiologically superior to nonapical pacing 4, 5…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our finding of lower cardiac mortality as well as death from pump failure with an apical LV lead position is in keeping with experimental and clinical studies showing that LV apical pacing is physiologically superior to nonapical pacing 4, 5…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings emerged from a subanalysis of the REVERSE (Resynchronization Reverses Remodeling in Systolic Left Ventricular Dysfunction) trial 3. These findings are counterintuitive, as previous experimental and clinical evidence shows that an apical LV lead position is more favorable than nonapical positions 4, 5. During normal sinus rhythm in intact myocardium, electrical impulses travel through the rapid conduction system from the His bundle toward the low apex.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the same way, a recent comparison of chronic RV apex and RV septal pacing, based entirely on lead position, showed that RV septal pacing was associated with more impaired circumferential strain and worse LV dyssynchrony than apical pacing (Ng et al, 2009). In contrast, it has been shown that the RV pacing site, which leads to the best LV function, is not predicted by anatomical position or by QRS duration (Peschar et al, 2003). The hemodynamic superiority of LV apex and LV septum pacing may be explained by a relatively physiological sequence of electrical activation when pacing from these sites (Mills et al, 2009;Peschar et al, 2003).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%
“…Inversely, in other animal studies (Mills et al, 2009;Peschar et al, 2003), it was demonstrated in canine hearts with normal ventricular conduction that LV function is maintained at SR level when pacing the LV apex or the LV endocardial surface of the interventricular septum (Mills et al, 2009;Peschar et al, 2003) and that electric desynchronization pacing was significantly greater in RV apical and RV septal than LV apical and LV septal pacing (Mills et al, 2009;Wyman et al, 2002). It was also demonstrated by using tagged magnetic resonance imaging that RV apex and RV septal pacing increased significantly mechanical dyssynchrony, discoordination (MRI tagging) and blood flow redistribution (microspheres) and reduced LV contractility, relaxation, and myocardial efficiency (stroke work/myocardial oxygen consumption).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%